2021
DOI: 10.1126/scitranslmed.abb2233
|View full text |Cite
|
Sign up to set email alerts
|

A self-amplifying loop of YAP and SHH drives formation and expansion of heterotopic ossification

Abstract: Heterotopic ossification (HO) occurs as a common complication after injury or in genetic disorders. The mechanisms underlying HO remain incompletely understood, and there are no approved prophylactic or secondary treatments available. Here, we identify a self-amplifying, self-propagating loop of Yes-associated protein (YAP)–Sonic hedgehog (SHH) as a core molecular mechanism underlying diverse forms of HO. In mouse models of progressive osseous heteroplasia (POH), a disease caused by null mutations in GNAS, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 78 publications
4
31
0
Order By: Relevance
“…Targeting dCas9-KRAB to putative enhancers or promoters recruits the H3K9 methyltransferase SET domain bifurcated histone lysine methyltransferase 1 (SETDB1), which increases local H3K9me3 binding and represses target gene expression. 33 As expected, dCas9-KRAB guided by sgRNA targeting the NF-kB p65 binding site in the POSTN promoter greatly reduced POSTN expression under TNF-a treatment (Figure 2M). In addition, we generated a luciferase reporter construct driven by the POSTN promoter (Figure S2B) and performed a dual-luciferase reporter assay.…”
Section: Mechano-stress Upregulates the Transcription Of Postn Via Nf...supporting
confidence: 75%
“…Targeting dCas9-KRAB to putative enhancers or promoters recruits the H3K9 methyltransferase SET domain bifurcated histone lysine methyltransferase 1 (SETDB1), which increases local H3K9me3 binding and represses target gene expression. 33 As expected, dCas9-KRAB guided by sgRNA targeting the NF-kB p65 binding site in the POSTN promoter greatly reduced POSTN expression under TNF-a treatment (Figure 2M). In addition, we generated a luciferase reporter construct driven by the POSTN promoter (Figure S2B) and performed a dual-luciferase reporter assay.…”
Section: Mechano-stress Upregulates the Transcription Of Postn Via Nf...supporting
confidence: 75%
“…Interestingly, rather than independently exerting their effects, the ERK and hedgehog signaling pathway displayed crosstalk between each other in HO‐ops upon osteogenic induction. The significance of hedgehog signaling pathway in trauma‐induced osteogenic milieu has also been confirmed in transgenic murine models by several scholars 31,32 . Likewise, in a study by Tu et al, ERK signaling has also been suggested to involved in the murine soft tissues HO formation downstream of Connexin 43 33 .…”
Section: Discussionmentioning
confidence: 84%
“…The significance of hedgehog signaling pathway in trauma-induced osteogenic milieu has also been confirmed in transgenic murine models by several scholars. 31,32 Likewise, in a study by Tu et al, ERK signaling has also been suggested to involved in the murine soft tissues HO formation downstream of Connexin 43. 33 Since ERK is also a master regulator highly linked to inflammation, targeting ERK signaling could reach a synergistic beneficial effect on wound healing.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Loss-of-function mutations in the GNAS gene cause progressive osseous heteroplasia (POH) (OMIM #166350), Albright hereditary osteodystrophy (AHO, OMIM #103580), or pseudo-pseudohypoparathyroidism (PPHP, OMIM #612 463) (Shore et al 2002), three rare autosomal dominant disorders. Loss of GNAS is characterized by progressive heterotopic ossification (HO) in extraskeletal soft tissue (Cong et al 2021). Although only a few clinical craniosynostosis cases due to loss of GNAS have been reported, infantile lethal cerebral infarction after surgery was documented (Leclercq et al 2018).…”
Section: Introductionmentioning
confidence: 99%